Regional Tax, Retributions, and Own-Source Revenues Performance of Bekasi City - Sueb, Memed; Mukti, Meliani; Yulita, Khairanis (Pusat P2M Politeknik Negeri Batam, 2025)
Tax reform in Indonesia is also addressing issues related to Regional Tax and Retributions (PDRD), which have become the major sources of regional own-source revenue (PAD). Therefore, this study aimed to analyze the effectiveness and contribution of regional tax to PAD in Bekasi City from 2017-2022 as well as project the potential tax and retributions between 2024-2028. The study procedures were carried out using rigorous techniques, such as descriptive analysis, ratio analysis, and forecasting. The results showed that there were fluctuations in the effectiveness of PDRD in Bekasi City for 6 years. The highest effectiveness of regional tax occurred in 2017 and decreased from 2018 to 2019, while retributions showed a significant difference. The results also showed that the contribution of the 2 variables to PAD of Bekasi City was in the low category. The most potential revenue projections for 2024-2028 were Acquisition Duty of Right on Land and Building (BPHTB) and Retributions for Fire Extinguisher Testing Services.